Endometritis in dairy cows reared in tropical conditions: microorganisms, risk factors, reproductive performance and natural alternative therapy - Paiano, Renan Braga (2021)
Uterine diseases reduce the profitability of dairy farms in addition to impairing the fertility of dairy cows. However, there is a lack of detailed information on the reproductive and productive performance of dairy cows affected by uterine diseases in tropical conditions, in addition to identification of factors and microorganisms associated with the occurrence of this disease. The importance of studies related to possible natural and unconventional treatments for uterine in replacement of antibiotic therapy is also highlighted. Thus, this thesis was structured in three studies: 1) Identify the main microorganisms present in the uterine environment of dairy cows with uterine diseases during the puerperium; 2) Identify the main factors associated with the occurrence of uterine diseases in dairy cows and assess the impact their impact on reproductive performance and milk production. 3) Evaluate the in vitro antibacterial action by disk diffusion assay of seven essential oils (rosemary, cinnamon, clove, eucalyptus, lemon, oregano and thyme) against the reference strains of Escherichia coli (ATCC 25922), Fusobacterium necrophorum (ATCC 25286) and Trueperella pyogenes (ATCC 19411). In study 1, the objective was to assess the main microorganisms related to cases of clinical endometritis (CE) and subclinical endometritis (SE) from uterine samples of dairy cows in Brazilian herds. Selective and differential media were used for isolation of aerobic and anaerobic bacteria and subsequent identification by mass spectrometry (MALDI-TOF MS). A total of 279 lactating Holstein cows with 28 to 33 days in milk from six commercial farms were evaluated. Initially, cows were classified in three groups: cytologic healthy cows (n = 161), cows with CE (n = 83), and cows with SE (n = 35). A total of 127 bacterial species of 48 genera were identified. Healthy animals presented 97 species, followed by the CE group with 53 identified species, while SE cows had only 21 bacterial species. There was a significantly higher isolation rate of Trueperella pyogenes in CE cows (26.5%) compared to healthy and SE cows. Some anaerobic species were exclusively isolated from the CE group. Interestingly, 18.1% of samples from CE cows and 40% of SE cows were negative to bacterial isolation. In study 2, the objective was to investigate the impacts of clinical endometritis and subclinical endometritis on the reproductive performance and milk production of cows reared in tropical conditions. A total of 279 lactating Holstein dairy cows (28 to 33 d in milk) from six commercial farms were studied. The animals were classified into three groups: healthy cows (without CE and SE, n = 161), cows with CE (vaginal discharge score = 3 and ≥ 18% PMNL, n = 83) and cows with SE (absence of signs of CE and > 18% PMNL, n = 35). Cows with CE had a lower conception rate at first AI (P < 0.05), and both cows with CE and SE required more services and days to be pregnant (P < 0.05), in addition to producing less milk than healthy cows (P < 0.05). No factor evaluated in this study was associated with the occurrence of CE and SE (P < 0.05). In conclusion, a negative impact of CE and SE on the reproductive performance and milk production of dairy cows was evidenced. In study 3, the antibacterial activity of seven essential oils against the reference strains of Escherichia coli, Fusobacterium necrophorum, Trueperella pyogenes and Staphylococcus aureus was investigated. The disk diffusion test revealed that the essential oils of cinnamon, clove, oregano and thyme showed presented a greater zone of inhibition against all bacteria evaluated. These findings indicate that essential oils have potential to be used as an alternative in the treatment of bovine endometritis. Overall, the findings of this thesis reveal the main microorganisms present in the uterine environment of cows with and without endometritis raised in tropical conditions. It was also found that clinical and subclinical endometritis impaired reproductive performance and milk production. Finally, essential oils have a strong antibacterial activity against the main microorganisms associated with uterine diseases in dairy cows.